Kecelakaan Menghambat Tumbuh dan Berkembang Suatu Bangsa - Handoko Suseno (CV. Publikasi Indonesia, 2022)
Traffic accidents on the highway have resulted in material and non-material losses. Traffic accidents also have an impact on increasing poverty due to maintenance costs, lost productivity, stress and prolonged suffering. The rapid growth in motor vehicle ownership in recent years, combined with the relatively young age of the population and the diversity of vehicle types, have resulted in a worsening of the accident problem. On a micro level, this is only seen as something that does not have a very significant impact and only becomes a problem for those experiencing it and their families. However, if similar cases are accumulated on a national scale, this certainly needs attention because it has a significant impact on the country. This research is a qualitative research. The data collection method used is by using a literature review.